Penalaran Aturan Hukum Perlindungan Identitas Agama pada Anak dalam Konsep Hadhanah di Malaysia - Fadani, Fadhil; Adib, Muhammad (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Issues in religious law and state law are inseparable from the pros and cons that conflict occurs, but the alignment in the Muslim majority society is religious, this raises an understanding of the character of religious values, one of which is to children. This study aims to educate children to behave according to religious teachings and morals. So it requires the concern of parents as the first education in the family environment, as for what is found in Malaysia is the rules regarding child custody or called hadhanah. This study analyzes the content of the existing hadhanah rules in Malaysia related to the protection of children's religion. This research uses a normative approach with the theory of maslahah mursalah put forward by Ibn Qayyim Al-Jauziyyah. This research is field research. The results of this study indicate that judges in the Syariah Court in deciding hadhanah cases make the child's religion a very important consideration. According to this article, the authors argue that the existence of hadhanah rules in Malaysia is a form of benefit in the framework of hifdz al-dinn at the hajiyah level. So as to provide religious understanding in accordance with Islamic values and principles in maintaining the religious identity of children and safety and justice.